Quality Assurance in Nursing Education - Shrestha, Tumla (Journal of Nursing Education of Nepal, 2011)
In all countries of the world, nurses are the largest group of healthcare professionals. The production of qualified nursing personnel is the responsibility of nursing institutes. Nursing institutions are required to develop their own mechanism for their quality assurance (QA) for quality nursing human resource production. QA can be internal and external. QA maintained by the institution itself is called internal quality assurance and by external agencies like nursing council is external quality assurance. For the internal QA, regular monitoring by the institute itself is necessary. Many institutes may not have a system of self-assessment for quality. So, this article is aimed to provide information to nursing institutes for internal quality assurance.